Flow-pressure patterns due to hand-water-interaction during a breaststroke-cycle represent change of volumetric energy density - Ungerechts, B. E.; Cesarini, D.; Ritter, Y.; Hermann, T. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
Swimming as a locomotion is a reaction to cognitively controlled limbs-water interaction, which creates non-steady local flow due to displacement of water and local change momentum of water mass, simultaneously. The induced flow represents a local change of volumetric energy density (VED) that is measured as local flow pressure change, which can be sensed and measured technically. Flow sensing is known as a highly relevant item for elite swimmers in order to manipulate the displaced water mass more efficient. Communicating verbally and/or showing how to manipulate flow effectively in detail is still a problem. The interactive sonification (ISon) of effects of hand-water-interaction (HWI) in real-time may help the situation. Elite breaststroke swimmers tested the new ISon device, aimed to improve the effect-symmetry of HWI while listening to changes of local flow pressure. Analysis of recorded local VED revealed that the tendency to achieve effect symmetry is weak, either per cycle or over adjacent plenty cycles. HWI, which are judged as simultaneous (parallel in time and path) in accordance with the rules, often do not produce symmetrical flow effects. This tackles the questions if effect-symmetry is biological feasible and a relevant feature of effective breaststroke. Findings show the need for further investigations and clarifying communication between practitioners and researchers of different fields.